2012
DOI: 10.1128/jcm.06219-11
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Genes Encoding Panton-Valentine Leukocidin Is Not the Primary Determinant of Outcome in Patients with Hospital-Acquired Pneumonia Due to Staphylococcus aureus

Abstract: The impact of Panton-Valentine leukocidin (PVL) on the outcome intested, (ii) presence of specific bacterial clone, (iii) levels of alphahemolysin, or (iv) delta-hemolysin production were identified. This study suggests that neither pvl presence nor in vitro level of alpha-hemolysin production is the primary determinant of outcome among patients with HAP caused by S. aureus. The Panton-Valentine leukocidin (PVL) is a bacteriophageassociated, bicomponent cytotoxin produced by some strains of Staphylococcus aure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 46 publications
5
26
2
Order By: Relevance
“…Only 3 of the 197 isolates encoding hla had RBC lysis activity with no detectable alpha-toxin detected by ELISA, whereas 32 of the 197 hla-positive isolates had detectable alpha-toxin by ELISA but not by the RBC lysis assay. These data suggest that previous reports using the RBC lysis assay may have underreported the prevalence of alpha-toxin in different S. aureus isolates (43). We observed that 89% of hemodialysis and 84% of postsurgical isolates produced alpha-toxin in vitro, suggesting that the potential for alpha-toxin expression is highly conserved.…”
Section: Figsupporting
confidence: 55%
See 1 more Smart Citation
“…Only 3 of the 197 isolates encoding hla had RBC lysis activity with no detectable alpha-toxin detected by ELISA, whereas 32 of the 197 hla-positive isolates had detectable alpha-toxin by ELISA but not by the RBC lysis assay. These data suggest that previous reports using the RBC lysis assay may have underreported the prevalence of alpha-toxin in different S. aureus isolates (43). We observed that 89% of hemodialysis and 84% of postsurgical isolates produced alpha-toxin in vitro, suggesting that the potential for alpha-toxin expression is highly conserved.…”
Section: Figsupporting
confidence: 55%
“…Assessment of in vitro alpha-toxin production was done by quantitative analysis of rabbit red blood cell (RBC) lysis as previously described by our group (43) and others (44,45). Briefly, 10 ml of tryptic soy broth (TSB; Becton Dickinson, Sparks, MD) in a 50-ml Falcon tube was inoculated with a loopful of culture from a fresh plate of each strain and incubated at 37°C and 220 rpm for overnight culture.…”
Section: Methodsmentioning
confidence: 99%
“…In the current study, there was a strong association between PVL positivity and increased mortality. The presence of PVL has been inconsistently associated with mortality (48,49). In fact, in the study by Haque et al, PVL negativity was associated with increased mortality on univariate analysis but was not an independent predictor of mortality (25).…”
Section: Discussionmentioning
confidence: 96%
“…35 Furthermore, we were unable to molecularly classify the MRSA isolates; molecular differences in MRSA strains have been shown to affect clinical results. [14][15][16] Susceptibility data and trough data were not available, and therefore it is not known if subjects reached therapeutic levels of the treatment agent.…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11]13,14 There are multiple differences among MRSA strains on a molecular level, including staphylococcal cassette chromosome mec (SCCmec) type, presence of the toxin Panton-Valentine leukocidin, and minimum inhibitory concentration, which can affect clinical outcomes. [14][15][16] MRSA pneumonia is a complex disease associated with significant morbidity and mortality. Despite the large public health impact of MRSA pneumonia, there are limited published data examining clinical predictors of success or failure.…”
Section: Introductionmentioning
confidence: 99%